Świadomość osób starszych na temat roli Nordic Walking w profilaktyce chorób przewlekłych = Awareness of the elderly about the role of Nordic Walking in the prophylaxis of chronic diseases - Kościńska, Elżbieta (Journal of Education, Health and Sport, 2016)
Kościńska Elżbieta. Świadomość osób starszych na temat roli Nordic Walking w profilaktyce chorób przewlekłych = Awareness of the elderly about the role of Nordic Walking in the prophylaxis of chronic diseases. Journal of Education, Health and Sport. 2016;6(12):29-37. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.192160 http://ojs.ukw.edu.pl/index.php/johs/article/view/4033 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 01.12.2016. Świadomość osób starszych na temat roli Nordic Walking w profilaktyce chorób przewlekłych Awareness of the elderly about the role of Nordic Walking in the prophylaxis of chronic diseases Elżbieta Kościńska Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Polska Słowa kluczowe: Nordic Walking, profilaktyka, seniorzy, świadomość. Key words: Nordic Walking, prophylaxis, elderly, awareness. Streszczenie Nordic Walking, to coraz bardziej powszechna forma aktywności fizycznej. Może być uprawiana w każdym wieku, również przez osoby starsze obciążone chorobami. Istniejące badania dowodzą jej pozytywnego wpływu na poprawę zdrowia i kondycji organizmu.W pracy podjęto próbę poznania poziomu świadomości osób starszych, na temat roli Nordic Walking, w profilaktyce chorób przewlekłych. Badaniami objęto 50 osób, w wieku 60 i więcej lat, nie uprawiających tej formy aktywności. W badaniach wykorzystano kwestionariusz ankiety, konstrukcji własnej. Analiza wyników badań pokazała, że świadomość badanych seniorów w tym zakresie jest bardzo niska, szczególnie wśród badanych mieszkających na wsi. Respondenci podali również, że nie planują uprawiania Nordic Walking. Biorąc pod uwagę fakt, że w naszym społeczeństwie wzrasta liczba osób po 60. roku życia, co często wiąże się z pogorszeniem stanu zdrowia, istnieje wciąż potrzeba promowania Nordic Walking, jako bezpiecznej formy aktywności fizycznej. Abstract Nordic Walking is becoming more and more common form of physical activity. It can be practised at any age, even by older people burdened with diseases. Already existing research prove its positive impact on the improvement of health and body condition. The study attempts to understand the level of awareness of the elderly on the role of Nordic Walking in the prophylaxis of chronic diseases. Research included 50 people in the age of 60 years old and more, not engaged in this activity. The study used an own designed questionnaire. Analysis of the results showed that awareness of the surveyed seniors on this subject is very low, especially amongst the respondents living in rural areas. Respondents also declared that they do not plan to practice Nordic Walking. Considering the fact that in our society the number of people over 60 years old increases, which is often associated with deterioration of health, there is still a need to promote Nordic Walking as a safe form of physical activity.